Antonymy in an Advertising Slogan (Proceedings of Southern Federal University. Philology, 2021)
Natalya B. Boeva-Omelechko  (Rostov-on-Don Russian Federation)The relevance of this work is due to the priority of such research areas as pragmalinguistics, the theory of persuasion, the theory of antonymy and the linguistics of creativity, as well as the need of further investigation of expressive potential of antonymy in extremely popular  advertising texts. The purpose of this work is to analyze the types of lexical, morphological, syntactic and text-based antonyms involved in creating advertising slogans in Russian and  English linguistic cultures. According to the results of the analysis of empirical material, these types include lexical systemic and individual author’s antonyms, antonymic postpositions, prepositions, grammatical forms representing categorical oppositions, inter-part-ofspeech antonyms, utterances based on antonymic models, words and phrases semantically equivalent to antonyms that form oppositions in a coherent text. Special attention is paid to the pragmatics of slogans with antonyms and to the language game performed with the help of antonyms of different types, as well as to the sources of creating individual author’s antonyms (words with peripheral antonymic semes, words with different spheres of use and emotional and expressive coloring, synonyms that turn into antonyms, precedent phenomena). The author comes to the conclusion that the creators of slogans try in every possible way to make unusual antonymic oppositions filled with a new meaning.Key words: advertising, slogan, antonym, expressiveness, persuasion.DOI 10.18522/1995-0640-2021-2-21-28